The Night as We Know It - Dike Nabila Trivinggar; Kurniawati Gautama; Iqbal Prabawa Wiguna (JURNAL RUPA, 2019)
Since the first invention of the light bulb, humans have increasingly been accustomed to living under excessive artificial light every night. Inappropriate use of artificial light causes light pollution that now affects more than 80% world’s population in densely populated cities, including Bandung City residents. The latest research shows that the rate of light pollution for a high category in Bandung City has experienced an increase of 13,79 km2/year during 2013-2017. This has resulted in the loss of Bandung night sky aesthetic because the lights coming from the ground form a skyglow dome in the atmosphere, blocking most of the astronomical object's light and rendering them invisible from earth. As a person who has always been interested in astronomy and is also a Bandung resident, I have concern over the long-lost Bandung night sky natural beauty due to light pollution caused by human activities. I desire to raise awareness of this issue through an installation art which explores lights, reflective paint, and video as the mediums.